2020
DOI: 10.1016/j.diii.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Interventional oncology at the time of COVID-19 pandemic: Problems and solutions

Abstract: The COVID-19 pandemic has deeply impacted the activity of interventional oncology in hospitals and cancer centers. In this review based on official recommendations of different international societies, but also on local solutions found in different expert large-volume centers, we discuss the changes that need to be done for the organization, safety, and patient management in interventional oncology. A literature review of potential solutions in a context of scarce anesthesiologic resources, limited staff and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 59 publications
(69 reference statements)
0
31
0
3
Order By: Relevance
“…At academic medical centers, diagnostic radiologists were able to work remotely using home work-stations. Some Interventional Radiology practices created teams of physicians, trainees, nurses and technologists to minimize cross-contamination of a potential exposure event ( 8 , 9 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…At academic medical centers, diagnostic radiologists were able to work remotely using home work-stations. Some Interventional Radiology practices created teams of physicians, trainees, nurses and technologists to minimize cross-contamination of a potential exposure event ( 8 , 9 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 Furthermore, it is difficult to apply a model of combined approach to priorities for HCC patients 14 : different tumors (for location and size) in different situations (well-preserved liver function or not) require different treatment strategies (HR or AT, open or laparoscopic surgery). 15 So, our multidisciplinary team as described in other experiences 16,17 played the role to adapt the therapeutic algorithm proposed by the actual guideline to the new emergency situation to select the best patient for the best treatment for HCC and, in the same time, to reduce the risk of COVID-19 infection for the patients as well as health professionals. Recent studies 18 cirrhotic patients with COVID-19 infection showed a poor outcome for either respiratory complications or liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…A targeted literature search was performed to identify PubMed-referenced publications pertaining to management of hepatocellular carcinoma in the setting of the COVID-19 pandemic as of May 6, 2020. 1,[3][4][5][6] A manual search of professional society websites identified existing guidelines (Table 1) as of the same date. These publications and guidelines were reviewed for recommendations related to surveillance and monitoring practices, and any available guidance was referenced to support the authors' recommendations when applicable.…”
Section: Methodsmentioning
confidence: 99%